VARIASI TUTUR PENERIMAAN DAN PENOLAKAN PEMBELI DALAM TRANSAKSI JUAL BELI BATIK DI PASAR GROSIR SETONO PEKALONGAN – KAJIAN SOSIOPRAGMATIK - Ika Arifianti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Communication is the most important aspect in human life whether in its process and social life of all people in the society. Communication is a process of sending information  with  its  all  aspects and  effects.  Therefore,  language  is  the  most important key to build the relation with others. There are two approaches used in this  research;  theoritical  approach  (using  socio-pragmatic  approach)  and methodological approach (using qualitative approach). The result of this research shows  that  there  are  speech  vatiations in  buyer’s  acceptance and  refusal in Sentono wholesaler market in Pekalongan. They are direct acceptance speech and indirect  acceptance speech.  Direct  acceptance speech  is  influenced  by  pragmatic effects such  as interest,  satisfaction,  and  symphaty.  While  indirect  acceptance speech  uses  pragmatic  functions  such  as (a)  persuading,  (b)  urging,  (c) convincing. There are also variations in direct and indirect refusal speech. Direct refusal uses  expressions  such  as  ‘ora’/’tidak’/’wis’/’tidak  usah’/’oralah’/ ‘tidaklah’.  While  indirect  refusal speech  includes:  (1) refusal without  refusal expression,  (2)  refusal  with  interjection,  (3)  alternative  refusal,  (4)  refusal  with excuses.Keywords: speech variation, language, socio-pragmatics